2022
DOI: 10.1002/pol.20220166
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐free terpolymerization of propylene oxide, carbon dioxide, and carbonyl sulfide: A facile route to sulfur‐containing polycarbonates with gradient sequences

Abstract: Introducing sulfur atoms into polycarbonate can improve its optical properties, but is limited by the lack of efficient synthetic methods. Here we develop a facile method to achieve the one‐pot/one‐step incorporation of sulfur atoms into polycarbonate chains using raw chemicals of propylene oxide (PO), carbon dioxide (CO2), and carbonyl sulfide (COS). The metal‐free Lewis acid–base pair composed of N, N‐dimethylcyclohexylamine combined with triethyl borane can effectively catalyze the terpolymerization of PO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Indeed, the work of Zhang/Zhang details the conversion of cyclic carbonates/COS to polythiocarbonates passing through the cyclic thiocarbonate intermediate compound. 29 As an interesting extension, in the latter work by Zhang/Zhang, 30 the authors reported terpolymerisation of propylene oxide, CO 2 and COS. The terpolymers obtained exhibited a high refractive index of up to 1.55, and as a result the authors proposed applications in the field of optical materials.…”
Section: Cyclic Monothiocarbonatesmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, the work of Zhang/Zhang details the conversion of cyclic carbonates/COS to polythiocarbonates passing through the cyclic thiocarbonate intermediate compound. 29 As an interesting extension, in the latter work by Zhang/Zhang, 30 the authors reported terpolymerisation of propylene oxide, CO 2 and COS. The terpolymers obtained exhibited a high refractive index of up to 1.55, and as a result the authors proposed applications in the field of optical materials.…”
Section: Cyclic Monothiocarbonatesmentioning
confidence: 90%
“…5c) as has been reported, for example, by Zhang/ Darensbourg and co-worker, 27 Ren and co-workers 28 and most recently in 2022 by Zhang/Zhang and co-workers. 29,30 In 2022, Coates and co-workers provided a good overview of this field of research in a review on multifunctional catalysts for ringopening copolymerisations. 31 In more detail, in the former two examples mentioned above, it is proposed that the catalysts produce the intermediate thiocarbonate in situ, which is then subsequently polymerised by ROP under the reaction conditions.…”
Section: Synthesis and Applications Of 13-oxathiolan-2-onesmentioning
confidence: 99%
See 1 more Smart Citation
“…The terpolymerization of PO with both CO 2 and COS has also been investigated recently. 95 Using Et 3 B/amine pairs, sulfur-containing polycarbonates with high molar masses ( M n up to 59 kg mol −1 ) and moderate dispersity ( Đ M < 1.56) could be obtained; by adjusting the COS feed, it was possible to adjust the thiocarbonate content in a range of 27–81%. Kinetic analyses showed that the polymer is characterized by a notable gradient (preferential incorporation of COS, Scheme 7 top).…”
Section: Triethylboranementioning
confidence: 99%
“…As one of the closest Et 3 B-analogues, Bu 3 B, which is also commercially available, has been employed in some cases and generally shows a very comparable behaviour to Et 3 B; 95,97 Zhang and co-workers noted that it may be beneficial on account of its increased size to further suppress side reactions when cyclic by-products can be formed via back-biting (i.e., copolymerization with CO 2 ). 89 Tri-sec-butylborane has been tested for the copolymerization of epoxides with TSI for polyurethane formation.…”
Section: Trialkyl-or Triaryl Monoboranesmentioning
confidence: 99%